The influence of E-WOM on purchase intentions in local culinary business sector - Alam Hamdani, Nizar; Abdul Fatah Maulani, Galih (International Journal of Engineering and Technology, 2018)
With a large population and high consumer interest in local culinary, Indonesia becomes a potential market for small and medium-sized local culinary enterprises. However, most of local small and medium-sized enterprises (SMEs) in culinary sector face a wide range of challenges especially when it comes to huge promotion costs. Fortunately, the ever-increasing numbers of Internet users in Indonesia provides an opportunity for these SMEs to promote their products through Electronic Word of Mouth (E-WOM). E-WOM can provide solutions for them since it has a quick and wide promotion reach. The purpose of this study is to find out the influencing factors of E-WOM on consumersâ€™ perceived quality and purchase decisions. This study used a descriptive and verification method. The samples include 76 followers of Instagram accounts of the local culinary enterprises based in Garut, Indonesia chosen using the probability, simple random sampling technique. To find out the influencing factors of E-WOM on the brand image, the data were analyzed using SPSS confirmatory factor analysis. Factors that are formed from the results of the analysis are product information and Emotions. In addition, a PLS method was carried out to explore the influence factors of E-WOM on consumersâ€™ purchase intention using SmartPLS software. Based on PLS calculation, it can be concluded that E-WOM has positive influence on purchase intention. Â